2008
DOI: 10.1021/jp800093j
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Oxidation and Decomposition of Dibenzofuran under Atmospheric Conditions

Abstract: The atmospheric degradation of dibenzofuran (DF) initiated by OH addition has been studied by using density functional theory (B3LYP method). Site C1 in DF is predicted to be the favored site for OH addition, with a branching ratio of 0.61 to produce a DF-OH(1) adduct. The calculated reaction rate constant for OH addition to DF has been used to predict the atmospheric lifetime of DF to be 0.45 day. Three different modes of attack of O2 ((3)Sigma(g)) on DF-OH(1) have been examined. Abstraction of hydrogen gem t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…A high hydroxylation activity was observed for Dbf, probably because of the presence of heterocyclic oxygen in the molecule, which may provide more reactivity to the aromatic rings and facilitate oxygenation (Altarawneh et al 2008). Several mono-and di-hydroxylated metabolites were detected after treatment of Dbf with monoxygenases of the ascomycetous mold Paecilomyces lilacinus (Gesell et al 2004) or with whole-cells of the zygomycete Cunninghamella elegans (Cerniglia et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…A high hydroxylation activity was observed for Dbf, probably because of the presence of heterocyclic oxygen in the molecule, which may provide more reactivity to the aromatic rings and facilitate oxygenation (Altarawneh et al 2008). Several mono-and di-hydroxylated metabolites were detected after treatment of Dbf with monoxygenases of the ascomycetous mold Paecilomyces lilacinus (Gesell et al 2004) or with whole-cells of the zygomycete Cunninghamella elegans (Cerniglia et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…CPs and phenol are the most important precursors in the gas-phase PCN formation [6][7][8][9][18][19][20]51]. In combustion and thermal processes, the phenolic-hydrogen of CPs and phenol can be abstracted by the active radicals H, OH, O( 3 P), and Cl to produce CPRs and PhR [51].…”
Section: Resultsmentioning
confidence: 99%
“…In combustion and thermal processes, the phenolic-hydrogen of CPs and phenol can be abstracted by the active radicals H, OH, O( 3 P), and Cl to produce CPRs and PhR [51]. Dimerization of CPRs or cross-condensation of PhR with CPRs to form chloro-DOHB intermediate are the initial and important step of PCN formation.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding value for the control experiment is −4.40 • C. Thus, the t is respectively 0.52 • C and 1.20 • C. Thus the H o and H p are −11.216 kJ mol −1 and −25.883 kJ mol −1 respectively according to Eq. (8). The H ion calculated is −1.240 kJ mol −1 with MPWB1K/6-311+G(3df,2p)//MPWB1K/6-31+G(d,p) method [34], which is more accurate than the B3LYP/6-311G**.…”
Section: The Influence Of the Orientation Of The Hydroxyl On Stabilitymentioning
confidence: 94%
“…But the reaction rates of PCDFs with NO 3 • and O 3 are so slow that the reaction with OH • is the primary pathway. So in the environment, polyhydroxylated dibenzofuran (PHODF) is an important degradation product of PCDF [8]. Manuela Gesell [9] found that in the soil, the biotransformation of the filamentous fungus Paecilomyces lilacinus can make the dibenzofuran (DF) hydroxylated.…”
Section: Introductionmentioning
confidence: 99%